Investigating the English Language Learning Motivation: An Interview Study - Arizah, Novarina Rachmi; Fatih Al Fauzi (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2025)
This study explores the motivational factors influencing English language learning among 7th-grade students at SMP 1 Islam Jember, addressing the issue of low student motivation and its impact on engagement and learning outcomes. Focusing on a specific cultural context, the research fills a gap by examining intrinsic motivation (personal interest, satisfaction, mastery) and extrinsic motivation (grades, praise, career opportunities) among middle school students. Using a qualitative approach, data were collected through semi-structured interviews and classroom observations involving 19 purposively selected students. Analysis followed Miles and Huberman’s model, including data reduction, display, and conclusion drawing. Findings reveal that intrinsic motivation, driven by positive experiences like understanding lessons and teacher appreciation, is more dominant. However, students with low self-confidence or facing challenges often lose motivation. Extrinsic motivation was evident in aspirations for high grades and using English for academic and professional purposes. The study concludes that interactive, relevant teaching strategies, such as incorporating popular media or project-based simulations, can significantly enhance motivation. These insights offer practical contributions for developing effective teaching methods to improve student engagement and learning outcomes.